A systematic review on antimicrobial and antiparasitic activity of Eurycoma longifolia Jack (Tongkat Ali) - Ab Latip, Mohd Qayyum; Mohd Noor, Mohd Hezmee; Ahmad, Hafandi; Abu Hassim, Hasliza; Salleh, Annas; Bejo, Mohd Hair; Zakaria, Alif Aiman (Hindawi, 2022)
Eurycoma longifolia or Tongkat Ali (family: Simaroubaceae) has the potential to be utilised as an antimicrobial and antiparasitic agent that correlated with its traditional use to treat jaundice, malaria, antiseptic agent, and many more. This review is aimed at systematically sieving through articles regarding the antimicrobial and antiparasitic activity of E. longifolia. A total of 123 studies have been found using suitable keywords and manually searched from previous studies through the four databases. After title screening and abstract examination, 56 articles were excluded due to duplication and not meeting the acceptance criteria. 67 articles were assessed on full-text accessibility, 31 studies remained, and this number decreased to 20 articles after a careful examination of the full-text articles. Among the 20 articles selected, 17 articles proved the potential of E. longifolia as an antimicrobial and antiparasitic agent efficiently. 2 selected articles showed partial positive results, which specified specific microorganisms tested. In contrast, another 1 article gave a completely negative result. As for the conclusion, current studies highlighted by this review may shed light on the future direction of studies concerning E. longifolia as a novel antimicrobial and antiparasitic agent. However, more research should be done in the future focusing on the efficiency of E. longifolia for veterinary medicine utilisation.